(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
This paper explores the application of smart contracts in enabling transparent, secure, and automated business process management by leveraging blockchain technology to execute predefined business rules autonomously, reduce reliance on intermediaries, enhance trust among stakeholders, improve process efficiency, ensure data immutability, and provide real-time auditability across organizational workflows.